Achievements and Challenges of CdS/CdTe Solar Cells - Zhou Fang; Xiao Chen Wang; Hong Cai Wu; Ce Zhou Zhao (International Journal of Photoenergy)
Thin film CdS/CdTe has long been regarded as one promising choice for the development of cost-effective and reliable solar cells. Efficiency as high as 16.5% has been achieved in CdS/CdTe heterojunction structure in laboratory in 2001, and current techniques for CdS/CdTe solar cells gradually step toward commercialization. This paper reviews some novel techniques mainly within two years to solve this problem from aspects of promotion of fabrication technology, structural modification, and choice of back contact materials.